PEMIKIRAN POLITIK JAMALUDDIN AL-AFGHANI (Respon Terhadap Masa Modern dan Kejumudan Dunia Islam) - Maryam, Maryam (JPP (Jurnal Politik Profetik), 2014)
Renewal of Afghani’s Islamic thought was based on the condition of the people and Islamic world, which esperienced social and religious backward. Jamaluddin al-Afghani, together with his Pan-Islamism was able to inspire Muslims and Islamic world to unite and to develop nasionalism among them.